THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, COMPANY SIZE, LEVERAGE, PROFITABILITY, GOOD CORPORATE GOVERNANCE, ON TAX AGGRESSIVENESS IN MANUFACTURING COMPANIES LISTED ON THE IDX FOR THE 2019-2022 PERIOD - Maharani Ayunarko; Herman Ernandi (International Journal of Economic Integration and Regional Competitiveness, 2025)
Objective: This study was conducted to examine the effect of Corporate Social Responsibility, Company Size, Leverage, Profitability, and Good Corporate Governance on Tax Aggressiveness in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for the period 2019–2022. Method: The population in this study consisted of food and beverage manufacturing companies listed on the IDX from 2019 to 2022. This study used 17 companies as samples selected using purposive sampling. The data in this study were obtained from several sources, such as annual reports and summary financial statements of companies in the research sample, which were obtained from the Indonesia Stock Exchange (IDX) database and www.idx.co.id. Hypothesis testing used descriptive statistical analysis, namely using the analysis of several models. Result: The results showed that corporate social responsibility, company size, and good corporate governance (institutional ownership) had a negative effect on tax aggressiveness in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the period 2019–2022. Meanwhile, leverage and profitability have a significant positive effect on tax aggressiveness in food and beverage manufacturing companies listed on the Indonesia Stock Exchange for the period 2019–2022. Novelty: The novelty of this study lies in its exploration of the relationship between Corporate Social Responsibility, Company Size, Leverage, Profitability, and Good Corporate Governance with tax aggressiveness, specifically in the context of food and beverage manufacturing companies listed on the IDX, offering new insights into how these factors interact to influence tax behavior in Indonesia.